Magnetic resonance parkinsonism indices and interpeduncular angle in idiopathic normal pressure hydrocephalus and progressive supranuclear palsy - Ugga, Lorenzo; Cuocolo, Renato; Cocozza, Sirio; Pontillo, Giuseppe; Elefante, Andrea; Quarantelli, Mario; Vicidomini, Caterina; De Pandis, Maria Francesca; De Michele, Giovanna; D’Amico, Alessandra; de Divitiis, Oreste; Brunetti, Arturo (Neuroradiology, 2020)
Purpose The clinical presentation of idiopathic normal pressure hydrocephalus (iNPH) may overlap with progressive supranuclear palsy (PSP). The Magnetic Resonance Parkinsonism Index (MRPI), MRPI 2.0, and the interpeduncular angle (IPA) have been investigated to differentiate PSP from healthy controls (HC) and other parkinsonisms. We aimed to assess equivalences and differences in MRPI, MRPI 2.0, and IPA in iNPH, PSP, and HC groups. Methods We retrospectively recruited 99 subjects (30 iNPH, 32 PSP, 37 HC) from two institutions. MRI exams, acquired on either 1.5 T or 3 T scanners, included 3D T1-weighted images to measure MRPI, MRPI 2.0, and IPA. Inter- and intra-rater reliability was investigated with the intra-class correlation coefficient (ICC), and the two one-sided t tests (TOST) procedure was used to assess these markers in iNPH, PSP, and HC. Results For all the three measures, intra-rater and inter-rater ICC were excellent (range = 0.91–0.93). In the comparison of iNPH and PSP with HC, differences for MRPI and MRPI 2.0 ( p < 0.01 in all cases) and no equivalence ( p = 1.00 in all cases) were found at TOST. iNPH and PSP MRPI showed no difference ( p = 0.06) and no equivalence ( p = 0.08). MRPI 2.0 was not equivalent ( p = 0.06) and not different ( p = 0.09) in the same two populations. PSP and HC IPA proved equivalent ( p < 0.01) while iNPH IPA was different ( p < 0.01) and not equivalent ( p = 0.96 and 0.82) from both PSP and HC. Conclusion MRPI and MRPI 2.0 significantly overlap in iNPH and PSP, with risk of misdiagnosis, and for this reason may not be helpful in the differential diagnosis.